Perceived Dignity of Advanced Cancer Patients and Its Relationship to Sociodemographic, Clinical, and Psychological Factors - Obispo, Berta; Cruz-Castellanos, Patricia; Hernandez, Raquel; Gil-Raga, Mireia; González-Moya, Manuel; Rogado, Jacobo; López-Ceballos, Helena; García-Carrasco, Miguel; Jiménez-Fonseca, Paula; Calderon, Caterina (Frontiers in Psychology, 2022)
Objective Loss of dignity is one of the main reasons for wishing for an early death in patients with incurable diseases such as cancer and is strongly associated with psychological distress and loss of quality of life. The present study aims to analyze the perceived dignity of patients with advanced cancer undergoing systemic treatment and their relationship with sociodemographic, clinical, and psychological factors. Methods A prospective, cross-sectional, multicenter study was conducted in 15 oncology departments in Spain. Patients with locally advanced, unresectable, or metastatic cancer who were candidates for systemic treatment were included. Participants completed demographic information and Palliative Patients’ Dignity Scale, Brief Symptom Inventory, Mental Adjustment to Cancer, Functional Social Support Questionnaire, and Illness Uncertainty. Results A total of 508 patients were recruited between February 2020 and October 2021. Most were male, aged > 65 years, with digestive tumors (41%), and metastatic disease at diagnosis. Subjects were classified as having low (56%, N = 283) or high (44%, N = 225) perceived dignity. Patients ≥ 65 years, with worse baseline status (ECOG ≥ 1), and worse estimated 18-month survival had lower levels of perceived dignity. People with lower perceived dignity scored higher for anxious preoccupation and hopelessness and lower for positive attitude. They also displayed higher levels of anxiety, depression, and somatic symptoms, greater uncertainty, and less social support. Conclusion Self-perceived dignity in advancer cancer patients is significantly associated with psychological factors, psychological distress, uncertainty, less social support. Knowledge of these specific interactions is importance for adequate, comprehensive palliative care.